Mechanisms controlling the silicon isotopic compositions of river waters - Georg, R; Reynolds, B; Frank, M; Halliday, A (2006)
It has been proposed that silicon (Si) isotopes are fractionated during weathering and biological activity leading to heavy dissolved riverine compositions. In this study, the first seasonal variations of stable isotope compositions of dissolved riverine Si are reported and compared with concomitant changes in water chemistry. Four different rivers in Switzerland were sampled between March 2004 and July 2005. The unique high-resolution multi-collector ICP-MS Nu1700, has been used to provide simultaneous interference-free measurements of 28Si, 29Si and 30Si abundances with an average limiting precision of ± 0.04‰ on δ30Si. This precision facilitates the clarification of small temporal variations in isotope composition. The average of all the data for the 40 samples is δ30Si = + 0.84 ± 0.19‰ (± 1σSD). Despite significant differences in catchment lithologies, biomass, climate, total dissolved solids and weathering fluxes the averaged isotopic composition of dissolved Si in each river is strikingly similar with means of + 0.70 ± 0.12‰ for the Birs,+ 0.95 ± 0.22‰ for the Saane,+ 0.93 ± 0.12‰ for the Ticino and + 0.79 ± 0.19‰ for the Verzasca. However, the δ30Si undergoes seasonal variations of up to 0.6‰. Comparisons between δ30Si and physico-chemical parameters, such as the concentration of dissolved Si and other cations, the discharge of the rivers, and the resulting weathering fluxes, permits an understanding of the processes that control the Si budget and the fate of dissolved Si within these rivers. The main mechanism controlling the Si isotope composition of the mountainous Verzasca River appears to be a two component mixing between the seepage of soil/ground waters, with heavier Si produced by clay formation and superficial runoff associated with lighter Si during high discharge events. A biologically-mediated fractionation can be excluded in this particular river system. The other rivers display increasing complexity with increases in the proportion of forested and cultivated landscapes as well as carbonate rocks in the catchment. In these instances it is impossible to resolve the extent of the isotopic fractionation and contributed flux of Si contributed by biological processes as opposed to abiotic weathering. The presence of seasonal variations in Si isotope composition in mountainous rivers provides evidence that extreme changes in climate affect the overall composition of dissolved Si delivered to the oceans. The oceanic Si isotope composition is very sensitive to even small changes in the riverine Si isotope composition and this parameter appears to be more critical than plausible changes in the Si flux. Therefore, concurrent changes in weathering style may need to be considered when using the Si isotopic compositions of diatoms, sponges and radiolaria as paleoproductivity proxies. © 2006 Elsevier B.V. All rights reserved.